Model-Based Leakage Estimation and Remaining Useful Life Prediction of Control Gas Cylinder - Zhenzhen Zhang; Hui Chen; Chao Qi; Yazhou Liu (International Journal of Aerospace Engineering)
The high-pressure gas cylinder is the pressure source for liquid propellant engine valve control. Leakage is a significant cause of pressure loss in gas cylinders, leading to engine control failure and serious flight accidents. In this paper, a model-based approach to estimate the leakage area and remaining useful life (RUL) of gas cylinders is proposed. To estimate the leakage area, a state space representation of the cylinder system is developed based on the nonlinear model derived from momentum, energy, and continuity equations. Leakage is defined as a system state, and an extended Kalman filter (EKF) as a state observer is implemented to estimate the leakage area. Internal pressure measurements of the gas cylinder are required as output parameters in the estimation process. Then, the estimated states are fed into the nonlinear model to iteratively calculate the RUL of the cylinder. To evaluate the effectiveness of the proposed method, scaling leakage test data, computational fluid dynamics (CFD) simulation results, and liquid rocket engine (LREs) hot test data are used. Calibration results have proved the validity and universality of the method, with the mean absolute error (MAE) for the remaining 80% useful life prediction results being less than 0.02, 0.04, and 1.10. This study can provide technical support for fault tolerance control and orbital replanning in case of control gas cylinder leaks.